"They're all gone": death trap at the "cheerful games". Issue 4 (4th July 2022) - Carmi, Udi; Levental, Orr
ABSTRACT: The Munich Olympic Games were an opportunity to present to the world the 'New Germany'. It was clear to everyone that the shadow of the Berlin Olympic Games would follow the Munich Olympic Games at every stage. This article deals with West Germany's attempts to erase Berlin 1936 from the public consciousness and to redesign Germany's image as a cosmopolitan, peace-seeking nation. Designing the new German image included innovative architectural design of the Olympic complex, concealing the prominent landmarks associated with the Nazi regime, visual design of the games in cosmopolitan spirit and opening ceremony without national pathos. Most notably absent were the armed security personnel at the Olympic village due to the fear of association that might be evoked by armed German soldiers. Yet reality struck the Germans in the face. The 'New Image' failed to hide the political disputes that arose during the games. The event was fraught with scandals with political overtones in addition to the massacre of the sportsmen by a terrorist organisation. The Games will forever be remembered due to the massacre and the rest of the scandals that occurred therein.